2017
DOI: 10.1016/j.jacbts.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat, Sugar Consumption, and Cardiorespiratory Fitness in Patients With Heart Failure With Preserved Ejection Fraction

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 46 publications
0
37
0
1
Order By: Relevance
“…HFpEF and very low NT-proBNP levels 375 retain a high degree of relevance for population of patients with HFpEF as obesity is an important and highly prevalent co-morbidity in this group. 24 These data, however, do not support elimination of NP assessment as part of routine management of HFpEF patients. Indeed, NPs remain strong markers of LV wall stress 25 and prognosis.…”
Section: Figurementioning
confidence: 96%
“…HFpEF and very low NT-proBNP levels 375 retain a high degree of relevance for population of patients with HFpEF as obesity is an important and highly prevalent co-morbidity in this group. 24 These data, however, do not support elimination of NP assessment as part of routine management of HFpEF patients. Indeed, NPs remain strong markers of LV wall stress 25 and prognosis.…”
Section: Figurementioning
confidence: 96%
“…A high‐fat diet can be divided into high‐unsaturated fat diet and high‐saturated fat diet. Data from clinical and preclinical studies showed that a high‐unsaturated fat diet consumption is related with an improved body composition and cardiac diastolic function in obese patients with heart failure with preserved ejection fraction (HFpEF), and in obese mice . Our previous studies have shown that 12 weeks of HFD consumption caused obese‐insulin resistance in rats .…”
Section: Introductionmentioning
confidence: 99%
“…Dietary sodium intake can affect fluid status and RAAS activation; therefore, we estimated sodium intake using a standardized 5-pass interview 24-hour dietary recall, as previously described. 10 Body weight and waist circumference were measured on the day of RAAS activation assessment. Waist circumference was measured according to the World Health Organization recommendations.…”
Section: Dietary Sodium Body Weight and Waist Circumference Assessmentioning
confidence: 99%